Tem wi-fi? - Silla, Vanessa Lubisco (2021)
This essay aims to add some elements and tools which were used in the creative process of the novel Tem wifi? To observe and analyze the relations established between the impact of tecnology at the current literature and its creative possible freedom in the academic supports are importante points which served to the narrative in general. The theoretical references used all along the work were diverse going from Roland Barthes to many online inquiries. Considering some aspects like design, Literature in Brazil, Creative Economy, Digital Humanities, among others were, essencial to reflect what we are living in terms of Pop Culture, which is always on the line to the future. The chosen proposal was fundamental to link the novel´s theme whose main character is a Youtuber, facilitating as well to bring up the discussed matter of identity search, in this case through Moroccan universe that served as a scenario to unmask human trafficking, an incessant crime, extremely abusive and uncontrollable.